Creating a culture, not just a space—A qualitative investigation into reflective practice groups in inpatient mental health settings from the perspectives of facilitators and attendees - Pui Lok Joshua Yiu; Abbie McDonogh; Harpreet Gill; Jo Billings (PLoS ONE, 2025)
Background Working in inpatient mental health settings is often characterised by highly emotive work and staff shortages. Despite the suggested benefits of reflective practice groups on staff well-being and clinical practice across healthcare settings, to date, there have been limited empirical studies on reflective practice groups in inpatient mental health settings, especially on group engagement and improvement. Methods We interviewed fifteen participants, including both facilitators and attendees of reflective practice groups. Participants were from eight inpatient mental health wards across two National Health Service settings in the UK. We analysed interview transcripts using thematic analysis. Result We deductively organised the data into themes and subthemes under three overarching domains–“Impact”, “Factors on Engagement”, and “Improvement”. Theme development was generated inductively from the data. For impacts, we found reflective practice groups may bolster staff reflective capacity and team cohesion. The groups may help attendees create appropriate distance from their emotions and overcome power hierarchies. We discovered that the availability of reflective practice, sense of containment in groups, and team composition may influence group facilitation and engagement. For improvements, different measures could be adopted to improve access and engagement of staff with difficulties attending. Facilitators may benefit from more support to establish a reflective culture and experiment with new ways of facilitating. Discussion Our findings add to the growing evidence base of the potential value of reflective practice groups in inpatient settings and elaborate on novel mechanisms of their potential impact. This study highlights changeable factors for engagement, concrete recommendations for improvements, and opportunities for further research.